Nanoencapsulation of lutein within lipid-based delivery systems: Characterization and comparison of zein peptide stabilized nano-emulsion, solid lipid nanoparticle, and nano-structured lipid carrier. (1st October 2021) - Liu, Mengyao; Wang, Fuli; Pu, Chuanfen; Tang, Wenting; Sun, Qingjie
Highlights: Zein peptides from trypsin (TZP) and flavourzyme (FZP) hydrolysis were prepared. Surface hydrophobicity of TZP was higher than that of FZP. Lutein-loaded NE, SLN, and NLC stabilized by TZP and FZP were fabricated. Carriers with TZP were more stable than those prepared from FZP. Bioavailability of lutein in SLN was the highest after in vitro digestion. Abstract: Three lipid-based carriers encapsulating lutein, nano-emulsion (NE), solid lipid nanoparticle (SLN), and nano-structured lipid carrier (NLC), were developed from zein peptides hydrolyzed by trypsin (TZP) and flavourzyme (FZP) as stabilizers. The physiochemical properties of FZP and TZP were evaluated. The particle size, potential, microstructure, environmental stability, rheological properties, in vitro digestion stability, and bioavailability of the lutein-loaded NE, SLN, and NLC were compared. The results showed that the surface hydrophobicity of TZP was higher than that of FZP. Except for the SLN, most samples were stable against droplet aggregation during storage, and carriers stabilized by TZP exhibited more favorable storage stabilities than those prepared from FZP. All the samples presented characteristics of fluid with good fluidity. The bioavailability of lutein was between 42.61% and 62.81%. In summary, these results provide valuable insights into the design of lipid-based delivery systems for fat-soluble biologically active compounds using zein peptides as stabilizers.